2014 25th International Workshop on Database and Expert Systems Applications 2014
DOI: 10.1109/dexa.2014.57
|View full text |Cite
|
Sign up to set email alerts
|

Keyphrase Extraction Abstracts Instead of Full Papers

Abstract: In the present paper 1 we consider keyphrase extraction problem from scientific articles. Finding an appropriate solution is important for the organization of fast navigation in databases, indexing, clustering and classification of academic papers. The base collection includes keyphrases selected by the experts for each text (SemEval2010). It is shown that the use of abstracts instead of full texts allows to improve the results obtained by processing full texts or abstracts with introduction and conclusion sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The noun phrase appears in many different patterns. In [24], the authors found 56 of these models from a training dataset. The important models are shown in Table 5.…”
Section: Review and Discuss Resultsmentioning
confidence: 99%
“…The noun phrase appears in many different patterns. In [24], the authors found 56 of these models from a training dataset. The important models are shown in Table 5.…”
Section: Review and Discuss Resultsmentioning
confidence: 99%